Concurrent 3D acquisition of diffusion tensor imaging and magnetic resonance elastography displacement data (DTI‐MRE): Theory and in vivo application. Issue 1 (20th January 2016) - Yin, Ziying; Kearney, Steven P.; Magin, Richard L.; Klatt, Dieter
Abstract : Purpose: To introduce a newly developed technique (DTI‐MRE) for the simultaneous acquisition of diffusion tensor imaging (DTI) and 3D‐vector field magnetic resonance elastography (MRE) data, and to demonstrate its feasibility when applied in vivo to the mouse brain. Methods: In DTI‐MRE, simultaneous encoding is achieved by using a series of diffusion/motion‐sensitizing gradients (dMSGs) with specific timing and directions. By adjusting the duration of the dMSGs with the diffusion time and with the mechanical vibration frequency, the shear wave motion and diffusion are encoded into the MR phase and MR magnitude signals, respectively. The dMSGs are applied in a noncollinear and noncoplanar manner that optimizes the capture of both the DTI signal attenuation and the three‐dimensional MRE displacements. In this work, the feasibility of the DTI‐MRE technique was demonstrated on in vivo mouse brains (n=3) using a 9.4T animal MRI scanner. The DTI‐MRE derived parameters (MD, mean diffusivity; FA, fractional anisotropy; MRE displacement fields; and shear modulus |G|) were compared with those acquired using conventional, separate MRE and diffusion methods. Results: The averaged (MD, FA, and |G|) values for three mice are (0.580 ± 0.050 µm 2 /ms, 0.43 ± 0.02, and 4.80 ± 0.06 kPa) and (0.583 ± 0.035 µm 2 /ms, 0.46 ± 0.02, and 4.91 ± 0.19 kPa) for DTI‐MRE, and conventional DTI and 3D‐vector field MRE measurements, respectively. All derived parameters (MD, FA, |G|, and displacement) obtained using the combined DTI‐MRE method and conventional methods were significantly correlated with P  < 0.05. Conclusion: Simultaneous acquisition of DTI and 3D‐vector field MRE is feasible in vivo and reduces the scan time by up to 50% compared with conventional, separate acquisitions, while providing an immediate co‐registration of maps of diffusion properties and stiffness. Magn Reson Med 77:273–284, 2017. © 2016 Wiley Periodicals, Inc.